Appraisal of healthcare students and professionals’ knowledge and intention to educate the public regarding monkeypox (Mpox) - Suliman Mohamed, Malik; Idriss, Mona Timan; Alotaibi, Nasser Hadal; Khan, Yusra Habib; Mallhi, Tauqeer Hussain (PeerJ, 2025)
Background In light of the increasing prevalence of monkeypox (Mpox) infections worldwide, it is critical to assess the level of awareness regarding the disease and its transmission among healthcare students and professionals. Understanding the knowledge gaps within these groups is essential, as they play a vital role in infection prevention and public education. Objectives This study aimed to assess healthcare students and professionals’ knowledge and intention to educate the public regarding Mpox. Methods An anonymous survey consisting of 37 items was constructed utilizing scientific information pertaining to Mpox, obtained from sources such as the World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), and previous studies. The study sample comprised healthcare professionals and students who were residents of the Al-Jouf province in Saudi Arabia. Significant associations between sociodemographic data and the knowledge and intention to educate the public about Mpox were compared using statistical methods. The comparison of means for two or more than two groups were performed using Student t-test and one-way ANOVA, respectively. Furthermore, ordinal logistic regression was employed for further analysis. Results Out of 545 responses, 437 (80.2%) were incorporated into the final analysis. Almost half of the participants in the study were female (51.5%) and 44.2% fell within the age range of 20 to 25 years. Moreover, 49.7% of the participants were unmarried and 29.5% held a bachelor’s degree. Over seven in ten participants were cognizant of the fact that Mpox is a public health emergency of international concern, whereas less than half of the participants were cognizant of the fact that Mpox has been reported in Saudi Arabia. The overall mean knowledge score was 10.40 ± 4.88 (score range: 0 to 21). Approximately 3.9% of the participants possess excellent knowledge (score > 17) and 44.9% possess average knowledge (score 12–17). The male gender, older participants, married, healthcare professionals and those in the medicine field were more knowledgeable. More than half of the study participants are willing to educate the public regarding Mpox, where overall intention score was 21.39 ± 6.84 (range 6 to 30). The female, married and those in the physiotherapy field showed more positive attitude and intention to educate the public regarding Mpox. Conclusions Despite the fact that the majority of participants had a high or moderate intention to educate the public about Mpox, their knowledge ranged from average to poor. In light of these findings, educational programs aimed at enhancing the knowledge and awareness of healthcare professionals and students regarding Mpox are required.
Keywords: Mpox; Knowledge; Intention; Healthcare professionals; Students